The Fusion of Fascia-Oriented Exercise and Pilates in Rollpilates Course at Masaryk University - Vychodilová, Renata; Pokorná, Alena; Vrtělová, Hana (Journal of Education, Health and Sport, 2016)
The aim of this paper is to analyse Pilates and fasia-oriented exercise in terms of their possible interconnection. We intend to introduce the fusion of Pilates and fascia-oriented exercise in the form of a new sports course Rollpilates lectured at the Faculty of Sports studies, Masaryk University, Brno. The course was formed in the project approved as part of the Masaryk University Development Fund and involves a nouveau approach towards the interconnection of two types of exercise. The methods include an analysis of scientific publications and educational materials dealing with Pilates and fascia-oriented exercise. In order to comprehend the theory and principles of fascia-oriented exercise and its interconnection with Pilates and to study new trends in Pilates, the work incorporates a bibliographic search, a research probe, the participation in several educational courses and the interviewing of experienced lectures of fascia-oriented and Pilates exercise, with the support of our own practical experience. Based on the analysis, a Rollpilates course was established and its programme, content and principles were defined. In order to enhance and propagate the course, educational online material was designed and displayed in the Information system of Masaryk University. Keywords: Rollpilates course, Pilates, fascia-oriented exercise, nouveau approach